In Vivo, Ex Vivo, and In Vitro Antihyperglycemic Evaluation of Croton ehrenbergii - Díaz-Román, Mónica Aideé; Rios, Maria Yolanda; Acevedo-Fernández, Juan-José; Aguilar-Guadarrama, A. Berenice (Planta Medica, 2025)
Various Croton species have been traditionally used to treat diabetes; however, the antidiabetic potential and safety of many of these species remain poorly understood. This study evaluated the chemical composition, antihyperglycemic activity, insulin-sensitizing effect, and acute oral toxicity of C. ehrenbergii. Dichloromethane, ethyl acetate, n-butanol, and aqueous residue fractions were obtained via liquid–liquid extraction from the hydroalcoholic extract obtained via maceration of the aerial parts. The primary compounds isolated from the fractions using column chromatography and identified by 1D nuclear magnetic resonance spectroscopy were 7,4′-di-O-methylnaringenin, β-sitosterol, tiliroside, rutin, nicotiflorin, isoquercetin, and l-quebrachitol. The in vivo antihyperglycemic activity of these compounds was assessed using oral sucrose and glucose tolerance tests, and the most active fractions were evaluated ex vivo to explore the mechanisms of action. The extract, fractions, and compounds were tested in vitro for their ability to inhibit α-glucosidase and protein tyrosine phosphatase 1B (PTP1B) as well as for their agonistic activity on PPAR-γ. Tiliroside and nicotiflorin moderately inhibited PTP1B and α-glucosidase; whereas, l-quebrachitol acted as a PPAR-γ agonist. Acute oral toxicity studies indicated that the extract was safe at the tested dose. These results provide the first scientific evidence of the antihyperglycemic properties and preliminary safety of C. ehrenbergii.
Keywords: Euphorbiaceae; Croton; Croton ehrenbergii; 7,4′-di-O-methylnaringenin; tiliroside; L-quebrachitol